Prosody and information status: analysis of production in brazilian portuguese - Alexandre Delfino Xavier (2014)
This study aims to assess which acoustic parameters are associated to the prosodic encoding of informational status in Brazilian Portuguese (henceforth BP). Three production experiments were conducted. In total, 13 people were instructed to read a series of narratives whose target words varied its status by their discursive context(given, new or accessible). After the recording sessions, the target words were stored in sound files. The duration of the target word (excluding the article), a central tendency measure (mean f0) and two dispersion measures (standard deviation and range of f0) ofwere analyzed. Data for analysis was extracted through Praat customized scripts and received statistical treatment. The results show that the duration and the mean f0 were the two most relevant parameters. In general, new referents have longer duration andreceive a higher f0 prominence on prestressed syllables compared to given and accessible referents. These last two statuses showed no significant differences between them.The overall analysis of the data from the studies indicates that the BP speakers actually use prosodic information to signal the informational status of entities in discourse.Despite the variation among subjects, one can notice that the acoustic differences between the statuses are stable within subjects. Unlike the results found in other languages (like German), BP seems to not have a distinctive marking for accessiblestatus, a conclusion which is supported by the data from both studies. Apparently, despite the fact that informational status is an inherently cognitive phenomenon, its manifestation is variable across languages.